Bacterial sensing underlies artificial sweetener‐induced growth of gut Lactobacillus. (4th August 2015) - Daly, Kristian; Darby, Alistair C.; Hall, Neil; Wilkinson, Mark C.; Pongchaikul, Pisut; Bravo, David; Shirazi‐Beechey, Soraya P.
Summary: Disruption in stable establishment of commensal gut microbiota by early weaning is an important factor in susceptibility of young animals to enteric disorders. The artificial sweetener SUCRAM [consisting of neohesperidin dihydrochalcone (NHDC) and saccharin] included in piglets' feed reduces incidence of enteric disease. Pyrosequencing of pig caecal 16S rRNA gene amplicons identified 25 major families encompassing seven bacterial classes with B acteroidia, C lostridia and B acilli dominating the microbiota. There were significant shifts in microbial composition in pigs maintained on a diet containing SUCRAM, establishing SUCRAM as a major influence driving bacterial community dynamics. The most notable change was a significant increase of Lactobacillaceae population abundance, almost entirely due to a single phylotype, designated L actobacillus 4228. The sweetener‐induced increase in L actobacillaceae was observed in two different breeds of pigs signifying a general effect. We isolated Lactobacillus 4228, sequenced its genome and found it to be related to L actobacillus amylovorus . In vitro analyses of L actobacillus 4228 growth characteristics showed that presence of NHDC significantly reduces the lag phase of growth and enhances expression of specific sugar transporters, independently of NHDC metabolism. This study suggests that sensing of NHDC by a bacterial plasma membrane receptor underlies sweetener‐induced growth of a health promoting gut bacterium.